Kinetics of Various 99mTc-Sn-Pyrophosphate Compounds in the Rat - Schümichen, C.; Mackenbrock, B.; Hoffmann, G. (Nuklearmedizin - NuclearMedicine, 1977)
The bone-seeking 99mTc-Sn-pyrophosphate compound (compound A) was diluted both in vitro and in vivo and proved to be unstable both in vitro and in vivo. However, stability was much better in vivo than in vitro and thus the in vitro stability of compound A after dilution in various mediums could be followed up by a consecutive evaluation of the in vivo distribution in the rat. After dilution in neutral normal saline compound A is metastable and after a short half-life it is transformed into the other 99mTc-Sn-pyrophosphate compound A is metastable and after a short half-life in bone but in the kidneys. After dilution in normal saline of low pH and in buffering solutions the stability of compound A is increased. In human plasma compound A is relatively stable but not in plasma water. When compound B is formed in a buffering solution, uptake in the kidneys and excretion in urine is lowered and blood concentration increased.It is assumed that the association of protons to compound A will increase its stability at low concentrations while that to compound B will lead to a strong protein bond in plasma. It is concluded that compound A will not be stable in vivo because of a lack of stability in the extravascular space, and that the protein bond in plasma will be a measure of its in vivo stability.